The occurrence and nature of early signs of schizophrenia and psychotic mood disorders among former child and adolescent psychiatric patients followed into adulthood - Rydelius Per-Anders; Engqvist Ulf (BMC, 2008)
Abstract Background This investigation was designed to characterize psychotic disorders among patients originally treated as in- and outpatients by child and adolescent psychiatric services and subsequently followed-up into mid-adulthood. The age at the first onset on symptoms, possible changes in diagnoses, early signs noted prior to or upon admission to child and adolescent psychiatric care and possible differences between patients with early- and later-onset disorder were of particular interest. Methods The study population consisted of patients (285 in- and 1115 outpatients) born between 1957 and 1976 and admitted to and treated by child and adolescent psychiatric care units in Jämtland County, Sweden, between 1975 and 1990. The status of their mental health was monitored until 2003 using official registries and hospital records. Diagnoses based on the ICD-8 and -9 systems, which were used in Sweden from 1968-1997, converted to diagnoses according to ICD-10, which has been in use since 1997. The Comprehensive Assessment of at Risk Mental States was employed to assess the information concerning psychopathology provided by the hospital records. Results By the end of the follow-up period 62 former child and adolescent psychiatric patients (36 females and 26 males), 4.4% of the entire study group, had received an ICD-10 diagnosis of "F20-29: Schizophrenia, schizotypal and delusional disorders" (48) and/or "F30-39: Psychotic mood disorders" (14). One-third (21) of these individuals were given their initial diagnosis of psychosis in connection with child and adolescent psychiatric care. Two of these 21 were not treated later for this disorder in general (adult) psychiatric care whereas the remaining 19 individuals were diagnosed for the same type of disorder as adults. The other 41 patients were diagnosed as psychotic only in connection with general (adult) psychiatric care. The mean age at the time of first onset of symptoms was 21.4 years (SD 6.4) and corresponding median age was 18. Behavioural changes and positive symptoms were the most frequent signs associated with a diagnosis of "F20-F29: Schizophrenia, schizotypal and delusional disorders" made during child and adolescent psychiatric care. In cases where a specific psychopathology developed later on the initial admission to child and adolescent psychiatry involved unspecified psychopathology. Conclusion In summary, it appears that psychotic disorders are relatively uncommon among patients admitted to child and adolescent psychiatric care in Sweden. However, individuals experiencing early onset of disorders categorized as "F20-29: Schizophrenia, schizotypal and delusional disorders" may already exhibit typical symptoms upon admission to child and adolescent psychiatric care of the age of 13-17; whereas late-onset disorders it appear not be associated with any obvious signs or symptoms years before the disorder has developed fully. Finally, certain cases of psychotic disorder during adolescence seem to have been episodic.